Fungsi Gelombang Pseudospin Simetri Untuk Potensial Rosen Morse Plus Coulomb Like Tensor Untuk Variasi q Dengan Menggunakan Metode Polymial Romanovski - Hidayatulloh, Alpiana; Zaidah, Alpi (Kappa Journal, 2023)
This study aims to determine the wave function of the Dirac equation of the Rosen Morse potential plus the coulomb type tensor potential for the pseudospin symmetry case using the Polynomial Romanovski method.Solving Dirac's equation using Romanovski polynomials is done by reducing the second-order differential equation to a hypergeometric type equation through variable substitution and the appropriate wave function. By comparing the second order differential equation of the hypergeometric type with the standard differential equation for the Romanovski polynomial, the relativistic energy equation and wave function are obtained. The symmetrical pseudospin wave function for the Rosen Morse potential is obtained from the weight function and expressed in Romanovski polynomial form.